Effects of thermal and nonthermal processing techniques on aroma compounds in fruit juices: A meta‐analysis. Issue 3 (8th December 2022) - Cheng, Chuanxiang; Wu, Yiwen; Yue, Jin
Abstract: Aroma compounds play important roles in juice flavor, and how some typical aroma compounds are affected by the processing techniques, in general, has not been unified. Thus, in this study meta‐analysis was used to evaluate the effects of the most widely used thermal (thermal pasteurization and high‐temperature short‐time) and nonthermal processing techniques (high hydrostatic pressure, ultrasound, pulsed electric field, and cold plasma) on four key aroma compounds in fruit juices: d‐limonene, (E)‐2‐hexenal, 1‐hexanol, and 1‐nonanol. Twelve studies were selected according to the set inclusion criteria, and the weighted response ratios ( R *) calculated by a random effect model. The study demonstrated that cold plasma ( R * = 1.08) and pulsed electric field ( R * = 1.17) technique resulted in an increase of d‐limonene levels, and high hydrostatic pressure ( R * = 0.95), thermal pasteurization ( R * = 0.74), ultrasound ( R * = 0.80), and high‐temperature short‐time ( R * = 0.77) technique caused a reduction of d‐limonene. The nonthermal techniques can reduce the degradation of the aroma compounds and may induce some chemical reactions to produce more aroma compounds, so that the overall flavor is better maintained than that processed after thermal techniques. This study can help the juice industry to seek processing techniques that can optimize flavor quality. Abstract : Meta‐analysis using response ratios was performed to assess the effects of seven generally used processing techniques on four key aroma compounds in fruit juices.